2013
DOI: 10.5772/57097
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Analysis of Fluid-Structure Interaction for a Biologically-Inspired Biped Robot Running on Water

Abstract: A kinematics analysis of a biologically-inspired biped robot is carried out, and the trajectory of the robot foot is understood. For calculating the pressure distribution across a robot foot before touching the surface of water, the compression flow of air and the depression motion of the water surface are considered. The pressure model after touching the water surface has been built according to the theory of rigid body planar motion. The multi-material ALE algorithm is applied to emulate the course of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Biped legged robot is inspired by the basilisk lizard that utilizes lift force instead of surface tension or buoyancy force to overcomes the weight of the body and propel it forward when the foot of the basilisk lizard splash on the water surface,while pushing the volume of water creates air vacuum which generates lift force and forward thrust. Xu et al [35] performed an analysis using fluid-structure interaction dynamics considering cylindrical coordinates, depression motion, and air compression flow on the water surface to obtain reaction pressure by water surface on foot when the feet slaps on the water surface. The biped robot accomplishes water walking with a forward thrust and lift force generated by an air pocket above and around the foot because of foot pressure displacing the water in a downward direction.…”
Section: ) Biped Amphibious Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biped legged robot is inspired by the basilisk lizard that utilizes lift force instead of surface tension or buoyancy force to overcomes the weight of the body and propel it forward when the foot of the basilisk lizard splash on the water surface,while pushing the volume of water creates air vacuum which generates lift force and forward thrust. Xu et al [35] performed an analysis using fluid-structure interaction dynamics considering cylindrical coordinates, depression motion, and air compression flow on the water surface to obtain reaction pressure by water surface on foot when the feet slaps on the water surface. The biped robot accomplishes water walking with a forward thrust and lift force generated by an air pocket above and around the foot because of foot pressure displacing the water in a downward direction.…”
Section: ) Biped Amphibious Locomotionmentioning
confidence: 99%
“…The leg mechanism of the legged Amphibious robot is serially connected links that undergo swing and stride phase, each link joint provides a single degree of freedom achieving reversibility over irregular terrain.The kinematic and dynamic models of the amphibious robots have different behavior on different environments while crawling on land and swimming in water. The kinematic analysis of bipedal robot is performed by Xu et al [35], the propulsion mechanism employs six bar plane Watt-I linkage mechanism as shown in Figure 2. The trajectory of point end effector G in the world coordinate frame is derived from Equation 1x G y G a…”
Section: E Kinematic and Dynamic Models Of Amphibious Robotmentioning
confidence: 99%
“…Some mature methods are utilized in the fault diagnosis of wheeled, legged, climbing and flying robots (Xu et al, 2013, 2015). For instance, Liu and Chen (2011) integrated Kalman filters and an expert system to diagnose several fault modes in corresponding movement states.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xu et al suggested another water-running robot that used a Watt-I linkage for the legs [21]. They also analyzed the dynamic performance of Water and ground-running robotic platform by repeated motion of six spherical footpads HyunGyu Kim, Dong Gyu Lee, Kyungmin Jeong, and TaeWon Seo, Member, IEEE B water-surface interaction theoretically [22]. Ground walking by lizards has been researched.…”
Section: Introductionmentioning
confidence: 99%